GERAKAN SADAR STUNTING: MENUJU MASA DEPAN INDONESIA BERKUALITAS - Angelina, Monica; Siswadi; Setiawan, Aris (LPPM Universitas Panca Bhakti, 2024)
The Stunting Awareness Movement: Toward a Quality Future for Indonesia is a community service program aimed at raising public awareness about the dangers of stunting and the importance of fulfilling children’s nutritional needs from an early age. Stunting is a serious health issue that can impede children’s physical and cognitive development and negatively impact the quality of future human resources. This program encompasses various activities, such as outreach, nutritional education, and training for communities and families, especially for pregnant women and families with young children. Through a participatory approach and collaboration with healthcare professionals, this movement aims to enhance public understanding of stunting and promote behavioral changes towards healthy living. The results of this initiative show an increase in community knowledge about stunting, as well as greater concern for child health and the importance of balanced nutrition.